Pocket reference to early rheumatoid arthritis - Emery, Paul (Springer Healthcare, 2011)
Written by a world-renowned expert in rheumatology this book serves as a refresher for GPs and hospital doctors containing practical diagnostic and treatment advice. Reviews clinical developments and guidelines, and places them into everyday clinical practice Stresses the importance of early and aggressive treatment Concise but comprehensive whilst being loaded with illustrations including imaging examples all presented in pocket sized format   Rheumatoid arthritis (RA) is the most common and serious inflammatory arthritis, resulting in joint destruction, functional impairment and increased mortality.  The outcome of the disease, however, has improved considerably in recent years with the availability of effective therapies and the recognition that early intensive treatment strategies result in better outcomes. This book has been designed to increase physician awareness of the importance of early and intensive treatment ? a key pharmaceutical strategy in rheumatoid arthritis.